2007
DOI: 10.1177/1368430207075154
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and Consequences of Satisfaction and Guilt Following Ingroup Aggression

Abstract: Three studies investigated the role of intergroup satisfaction in intergroup conflict. After reading about real acts of aggression committed by an ingroup, participants reported how those actions made them feel and how much they would support similar aggression in the future. In all three studies, experiencing intergroup satisfaction increased support for similar aggression, whereas experiencing intergroup guilt decreased support for si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
62
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 44 publications
(56 reference statements)
0
62
0
Order By: Relevance
“…Maitner, Mackie, and Smith (2007), for example, found that people experience increased satisfaction about aggressive in-group actions following the use of exonerating cognitions to excuse and justify this behavior. Numerous studies report that individual moral disengagement strategies such as attribution of blame (e.g., Doosje & Branscombe, 2003;Roccas et al, 2006) and dehumanization (e.g., Castano & Giner-Sorolla, 2006;Leidner et al, 2010) are frequently used to inhibit or attenuate negative groupbased emotions.…”
Section: Assessing Convergent and Discriminant Validity Of The Mdishmentioning
confidence: 99%
“…Maitner, Mackie, and Smith (2007), for example, found that people experience increased satisfaction about aggressive in-group actions following the use of exonerating cognitions to excuse and justify this behavior. Numerous studies report that individual moral disengagement strategies such as attribution of blame (e.g., Doosje & Branscombe, 2003;Roccas et al, 2006) and dehumanization (e.g., Castano & Giner-Sorolla, 2006;Leidner et al, 2010) are frequently used to inhibit or attenuate negative groupbased emotions.…”
Section: Assessing Convergent and Discriminant Validity Of The Mdishmentioning
confidence: 99%
“…So, for example, individuals who are asked to think about themselves as women, say, or as Americans, show far more similarity in the specific emotions they report experiencing than they do when explicitly asked to think about themselves as unique individuals. In both cases, whether group-based emotions are chronic and general or acute and event specific, group members more highly identified with the group show such effects more strongly than those less identified with the group (e.g., Maitner, Mackie, & Smith, 2007;Smith et al, 2007).…”
mentioning
confidence: 99%
“…The experience of collective guilt motivates a desire to compensate the harmed outgroup or avoid similar behavior in the future (Doosje, Branscombe, Spears, & Manstead, 1998). Finally, satisfaction with an action taken toward another group motivates a desire to engage in similar behavior in the future (Maitner et al, 2007). Thus, a range of intergroup emotions has been shown to motivate the desire for specific intergroup behaviors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, unsatisfactory retaliation following the experience of intergroup anger may result in increased desire to retaliate (Maitner, Mackie, & Smith, 2006). However, future desire for intergroup aggression will be reduced if in-group members of a perpetrator group feel a strong sense of guilt compared with those with low guilt (Maitner, Mackie, & Smith, 2007).…”
mentioning
confidence: 99%